2020
DOI: 10.3390/ijerph17103633
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Impacts of the Trident Copper Mine Project in Northwestern Zambia: Results from Repeated Cross-Sectional Surveys

Abstract: The application of a health impact assessment (HIA) for a large-scale copper mining project in rural Zambia triggered the long-term monitoring and evaluation of determinants of health and health outcomes in communities living in proximity to the mine. Three consecutive cross-sectional surveys were conducted at intervals of four years; thus, at baseline (2011), four (2015) and eight (2019) years into the project’s development. Using the same field and laboratory procedures, the surveys allowed for determining c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…All these dimensions, alongside broad social engagement, need to be carefully incorporated when assessing health impacts, particularly in the dynamic setting of industrial mining projects [ 5 , 29 , 42 ]. A seminal study pertained to community health in mining regions monitored the health status of population in vicinity of a copper mine over time [ 8 ]. The researchers reported improvement of certain health conditions in mining communities compared to control groups, including reduced risk for malaria and less parasitic infections in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these dimensions, alongside broad social engagement, need to be carefully incorporated when assessing health impacts, particularly in the dynamic setting of industrial mining projects [ 5 , 29 , 42 ]. A seminal study pertained to community health in mining regions monitored the health status of population in vicinity of a copper mine over time [ 8 ]. The researchers reported improvement of certain health conditions in mining communities compared to control groups, including reduced risk for malaria and less parasitic infections in children.…”
Section: Discussionmentioning
confidence: 99%
“…HIA, which is poorly institutionalised in sub-Saharan African countries [ 30 ], or the inclusion of health in other forms of impact assessment should go beyond a mechanism to obtain the mining licence and also encompass participatory monitoring and follow-ups [ 62 , 63 ]. As inclusive and participatory tool, HIA should inform community development initiatives including health interventions for local communities, and further contribute to sustained health improvements [ 8 ]. Meanwhile, this could strengthen Corporate Social Responsibility (CSR), which serves as umbrella term for various community development initiatives under the lead of the mining companies [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from single-country analyses point at positive impacts of mining projects on child nutrition in Mali but negative effects in Tanzania [ 20 ], while in a case study in Zambia no effect was found [ 27 ]. Similarly, the findings on the impact on diarrheal diseases are inconclusive [ 20 , 21 , 28 ]. In Zambia, the burden of diarrhea-causing parasitic infections decreased in mining areas [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have linked activities of the resource extraction with increased incidence of respiratory diseases [ 13 , 14 ]; sexually transmitted infections, including HIV/AIDS [ 15 ]; malnutrition [ 16 ]; vector-related diseases [ 17 , 18 , 19 ]; mental health [ 20 , 21 ]; and cancer diseases [ 9 ]. On the other hand, resource extraction projects can positively contribute to population health through improved labor market opportunities and corporate social responsibility (CSR) activities that support local health systems or contribute to general health and education programs [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%